1999
DOI: 10.1007/s001670050183
|View full text |Cite
|
Sign up to set email alerts
|

Fractures of the fifth metatarsal in basketball players

Abstract: A prospective nonrandomized study was made of 17 basketball players with fractures of the proximal third of the shaft of the fifth metatarsal. Eight had acute fractures, which were treated with a cast without weight-bearing, and the other nine had stress fractures for which percutaneous compression screwing was initially used. In the first group, union was obtained in four cases in an average of 9 weeks, with resumption of sport by 12 weeks. Three had a good outcome and the fourth was fair. The other four case… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
28
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(29 citation statements)
references
References 22 publications
(70 reference statements)
1
28
0
Order By: Relevance
“…These Wnd- Table 1 Biomechanical muscle strength measurement The results show no signiWcant diVerence for eversion strength and the ES/IS ratio. However, a slight signiWcant diVerence could be seen for the inversion strength The results show no signiWcant diVerence for maximal ground reaction force, ground contact time, peak pressure and contact area from the aVected to the nonaVected contralateral foot ings were consistent with previous reported data [2,8,9]. The radiographic healing was found mainly between 6 and 12 weeks.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…These Wnd- Table 1 Biomechanical muscle strength measurement The results show no signiWcant diVerence for eversion strength and the ES/IS ratio. However, a slight signiWcant diVerence could be seen for the inversion strength The results show no signiWcant diVerence for maximal ground reaction force, ground contact time, peak pressure and contact area from the aVected to the nonaVected contralateral foot ings were consistent with previous reported data [2,8,9]. The radiographic healing was found mainly between 6 and 12 weeks.…”
Section: Discussionsupporting
confidence: 91%
“…The radiographic healing was found mainly between 6 and 12 weeks. Similarly, Reese et al [10] and Portland et al [9] reported healing times within 6-8 weeks, Fernandez et al within 8-14 weeks [2]. Although complications like nonunion and persistent pain have been reported [11], this was found to happen mainly in cases in which return to competition was forced.…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…10,11 Speculation exists that the increased medial support in modern basketball shoes may be a contributing factor to the increased incidence of a fifth metatarsal fracture. Other factors in footwear design, such as flexibility, cushioning, and fit, may also have effects on the stresses being placed on the fifth metatarsal during different athletic tasks.…”
mentioning
confidence: 99%